Social Problems - Doob, Christopher Bates (Harcourt Brace College Publishers, 1995)
[This book] focus[es] on topics [such as:] the corporate state, an emphasis on the impact of the power elite in a capitalist state; the environment, pollution and depletion of resources, with a new sense of urgency created for alleviating if not solving these chronic problems; urban deterioration, the steady decline in the physical and cultural quality of city life, with little successful effort to plan cities with citizens' basic needs and interests in mind; racism, the legacy of our nation's racist past carrying into the present and still impacting heavily on many citizens, most notably the minority poor; sexism, men's traditional domination of women ... youth problems, a variety of major difficulties facing many young people [and] crime, an analysis of some of the most disturbing, damaging types of crime ravaging the modern United States. These subjects are examined in depth, with diverse, primarily recent source material used. -Pref.
Keywords: Social problems; Sociology; dept.soc; faculty_collection